REKONSTRUKSI SISTEM SOSIAL DALAM CERPEN PENGARANG BALI - I.B Putera Manuaba (Humaniora, 2009)
The findings of this study: first, in their short stories was offered a revision to the existing Balinese social system, that is, an egalitarian and democratic; they also offer a construct of ordinary people without any hierarchy. Second, the change that make in their short stories is still concerned with experimentations in peripheral areas, which are subjective, tend to be disfunctional, and do not seem to touch the essential. Third, there is influence of the social world of the authors on the social world of their works; the social system in which they live strongly determines the construction of the social world in the short stories.